THE RELATIONSHIP BETWEEN DISTRIBUTION OF BRYOPHYTES AND SOIL CONDITIONS ON DEGLACIATED ARCTIC TERRAIN IN NY-ÅLESUND (17th Symposium on Polar Biology) - ミナミ, ヨシノリ; カンダ, ヒロシ; マスザワ, タケヒロ; MINAMI, Yoshinori; KANDA, Hiroshi; MASUZAWA, Takehiro (National Institute of Polar Research, 1996)
P(論文) The relationship between distribution of bryophytes and soil conditions on deglaciated arctic terrain in front of East Brogger glacier in Ny-Alesund, Spitsbergen, Svalbard was studied. Vegetation was divided into four community types, i.e. 1) moraine community, 2) Saxifraga community (dominated by Saxifraga oppositifolia), 3) Dry as community (dominated by Dry as octopetala), and 4) wetland community, based on the vegetation map by I. BRATTBAKK (Vegetation Map 1:10000, Museet, Bot. avd., Trondheim, 1981). We established study sites randomly in each community (18, 27, 26 and 23 sites respectively), carried out vegetation analysis and sampled soil. Six patterns were observed in the frequency of major species in the four communities. In soil chemistry, total nitrogen concentration was low, and soil pH and EC were high, with soil pH approximated neutral, in the moraine community. Mg and Zn content were also high in the moraine community. Conversely, Al content was highest in the Dryas community and lowest in the moraine community. It was considered that the soil conditions on the moraine were distinctive, and greatly influence the bryophytes growing there. departmental bulletin paper